Computation of cavity shapes, sizes, and plasticities - Comba, Peter; Okon, Norbert; Remenyi, Rainer (Journal of computational chemistry, 1999)
A new molecular mechanics approach has been developed and used to scan the optimum geometry (size and shape) of a host molecule and the energy cost for the deformation of the bonding cavity, based on a general, unspecific guest with given docking sites and a variable size. Lagrange multipliers are used to constrain the sum of internal coordinates (host-guest docking-site distances), and no assumptions with respect to the type and strength of the host-guest bonding have to be made. This new approach has been fully implemented in a molecular mechanics program, and it is used to compute the size, shape, and plasticity of a rigid, asymmetrical, tetradentate (Namine)2(Npyridine)2 ligand. It is shown that all other methods for the computation of ligand hole sizes that have been reported so far are not able to compute the ligand cavities independently of the metal ion, and they lead to strikingly different shapes, sizes, and plasticities.
Gesehen am 13.03.2018